Selection of In Vivo Relevant Dissolution Test Parameters for the Development of Cannabidiol Formulations with Enhanced Oral Bioavailability - Nathan Koch; Quentin Bourcy; Olivier Jennotte; Patrice Chiap; Anna Lechanteur; Jean-Michel Cardot; Brigitte Evrard (Pharmaceutics)
Background: Cannabidiol (CBD) shows interesting therapeutic properties but has yet to demonstrate its full potential in clinical trials partly due to its low solubility in physiologic media. Two different formulations of CBD (amorphous and lipid-based) have been optimized and enable an increase in bioavailability in piglets. In vivo studies are time-consuming, costly and life-threatening. Therefore, we need to develop in vitro tests that can predict what will happen in vivo. Methods: Comparisons in terms of dissolution were made especially by using different media (FaSSGF, FaSSIF, FeSSIF, HCl 0.1N with or without SLS, phosphate buffer pH 6.8 with or without SLS) and different conditions (sink or non-sink conditions). These in vitro results were confronted with in vivo results to select the most appropriate dissolution test conditions. Results: The importance of the presence of surfactants to enable solubilization of CBD was demonstrated. Neutral media enabled a relatively good prediction of the extent of absorption observed in vivo, whereas the rate of absorption was more complicated to predict. Conclusions: FeSSIF media, and FaSSIF sink media to a lesser extent, were the only compositions enabling predictions of both extent and rate, indicating that emulsification is possibly a major contributor to the in vivo availability of the drug.